Alberta : showing oil and gas fields and potential oil and gas areas - Geological Survey of Canada (Surveyor)
This map shows oil and gas fields and pipelines, refineries, potential areas, First Nations reserves, railroads, cities and towns in Alberta in 1953. "Map 1039A" Scale 1:1,267,200, or 20 miles to 1 inch. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . Inset: [Regional map of Alberta showing pipelines]. Shows oil and gas fields and pipelines, refineries, potential oil and gas areas, First Nations reserves, railroads, cities and towns.